2001
DOI: 10.1152/ajpregu.2001.280.1.r149
|View full text |Cite
|
Sign up to set email alerts
|

Cold-induced changes in thyroid function in a poikilothermic mammal, the naked mole-rat

Abstract: Cold acclimation induces very divergent responses in thyroid function in reptiles and mammals reflective of their different thermoregulatory modes. Naked mole-rats, unlike other small mammals, are unable to effectively employ endothermy and are operatively poikilotherms. We therefore investigated changes in their thyroid status with chronic cold exposure. Under simulated burrow conditions, free thyroxine (T(4); 0.39 +/- 0.09 ng/dl) and thyroid stimulating hormone (TSH; 1.12 +/- 0.56 microIU/ml) levels fell wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 36 publications
2
47
1
1
Order By: Relevance
“…In small to medium sized eutherian mammals TT4 is typically is in the range 20–80 nmol L −1 (Hulbert, 2000), and TT4 of active echidnas is 15 nmol L −1 (Hulbert and Augee, 1982; Nicol et al, 2000), at the low end of the normal range for eutherian mammals and consistent with a low metabolic rate. The only significantly lower TT4 for an adult small mammal comes from a poikilothermic rodent, the naked mole-rat ( Heterocephalus glaber ), with a TT4 of 5 nmoL −1 , which increases to 7 nmol L −1 during cold exposure (Buffenstein et al, 2001). …”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…In small to medium sized eutherian mammals TT4 is typically is in the range 20–80 nmol L −1 (Hulbert, 2000), and TT4 of active echidnas is 15 nmol L −1 (Hulbert and Augee, 1982; Nicol et al, 2000), at the low end of the normal range for eutherian mammals and consistent with a low metabolic rate. The only significantly lower TT4 for an adult small mammal comes from a poikilothermic rodent, the naked mole-rat ( Heterocephalus glaber ), with a TT4 of 5 nmoL −1 , which increases to 7 nmol L −1 during cold exposure (Buffenstein et al, 2001). …”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…Thyroid hormones in wild animals may vary considerably with season (especially in temperate regions), food availability, habitat (e.g., subterranean versus above ground dweller), and stages of life history (e.g., hibernation). It appears that, at least for prolonged periods of time, long-lived squirrels, deer mice, bats and mole-rats maintain low levels of thyroxine (Lyman et al, 1982; Hulbert et al, 1985; Kwiecinski et al, 1986; Buffenstein et al, 2001). Life extension effects associated with sustained low thyroid hormone levels have been reported in rats, whereas a reduction in lifespan occurs with sustained hyperthyroid levels (Ooka and Shinkai, 1986).…”
Section: Hormone Profilesmentioning
confidence: 99%
“…Low thyroid hormone concentrations may help to explain this thermoregulatory mode. 32 Intriguingly, an immunocytochemical and ultrastructural study of NMR pancreas showed that the alpha (glucagon-producing) and beta (insulin-producing) distribution differed from that of other rodents and of humans, in that beta cells formed the mantle while alpha cells formed the internal core of the islets. 33 Moreover, strange enough NMR are insulin insensitive and they have abnormal responses to glucose tolerance tests.…”
Section: Metabolismmentioning
confidence: 99%